Analysis on Flavor Quality of Brassica rapa L. from Different Varieties - MAERHABA·Paerhati; Zhanteng SONG; Ruina YANG; Jing LI; Jing AN; Min LIU; Zhenzhen XU; Jingrong ZHU (Shipin gongye ke-ji)
Analysis the flavor quality of Brassica rapa L. from different varieties, in order to provide theoretical basis, which study on quality evaluation and improvement of flavor quality. The volatile flavor compounds were detected by gas chromatography-ion mobility spectrometry (GC-IMS). The content of 17 kinds of amino acids in Brassica rapa L. was determined by automatic amino acid analyzer, and Brassica rapa L. flavor was evaluated with sensory evaluation method. GC-IMS results showed that 68 volatile flavor components, including testers, alcohols, aldehydes and sulfur, were identified in SFB, RQH, KPZ, and KPB. There were some high aroma compounds such as (Z)-3-hexenol, dimethyl disulfide, 3-pentanone (D), acetone, propionaldehyde and 2-phenylethyl isothiocyanate. Through PCA and GC-IMS, it was good to distinguish among 4 different varieties of Brassica rapa L.. Results showed that the amino acids in 4 different varieties of Brassica rapa L. were all of various kinds, all containing 17 amino acids measured, including 7 essential amino acids for human body. The umami amino acids of SFB accounted for a relatively high proportion, and the sweet amino acids of KPZ accounted for a relatively high proportion. The highest comprehensive score of sensory evaluation was KPZ, followed by RQH. The flavor quality of Brassica rapa L. from different varieties were evaluated based on volatile flavor compounds, flavor amino acids and sensory evaluation, and the differences in flavor and quality among different Brassica rapa L. were clarified.